Audit committee effectiveness, internal audit function and sustainability reporting practices - Zainabu Tumwebaze; Juma Bananuka; Twaha Kigongo Kaawaase; Caroline Tirisa Bonareri; Fred Mutesasira (AJAR (Asian Journal of Accounting Research), 2022)
Purpose – The purpose of this study is to examine the association between audit committee effectiveness (ACE), internal audit function (IAF) and sustainability reporting practices. Design/methodology/approach – Using a cross-sectional and correlational design, useable questionnaires were received from 48 financial services firms in Uganda. The data were analyzed using Statistical Package for Social Sciences. Findings – results indicate that ACE and IAF are positively and significantly associated with sustainability reporting practices. ACE and IAF are more significantly associated with economic and social indicators than environmental sustainability indicators. Research limitations/implications – In terms of practice, it is no longer a matter of having internal auditors and audit committees in place but rather those who are mindful of the welfare of society and the natural environment. The effectiveness of the board audit committee and a functioning internal audit can be assessed in terms of their recommendations and decisions regarding improvements in the welfare of society and the natural environment in addition to the traditionally known performance benchmarks. Practical implications – The study focuses on only financial services firms in Uganda, and this is a small sample. Future studies may focus on larger samples to enable comparison of the results. Originality/value – This study provides insights on the initial understanding of the association between ACE, IAF and sustainability reporting practices using evidence from a developing African country – Uganda.